Ambitions and Limits of Financial Disintermediation in the Euro Area - Grégory Levieuge; Jean-Paul Pollin (Vierteljahrshefte zur Wirtschaftsforschung, 2017)
This paper deals with the causes and consequences of the financial disintermediation that for some time has been taking place in Europe, particularly since the last financial crisis. Firstly, we present the evolution of bank and capital markets funding, which can be largely explained by the singular economic context we have experienced since 2008. Secondly, we analyse the objectives pursued by some national and European institutions, which campaign for more disintermediation against what they consider to be "overbanking". Finally, we critically analyse the effects of disintermediation in terms of access to funding for (small) companies, as well as its impact on economy and financial stability. – – Dieser Beitrag setzt sich mit den Ursachen und Konsequenzen von Disintermediation im Finanzsektor auseinander. Der seit einiger Zeit in Europa zu beobachtende Trend zur Disintermedation hat sich in den Krisenjahren seit 2008 verstärkt. Zunächst untersuchen wir, welche Entwicklung die Bank- und Kapitalmarktfinanzierung seit 2008 genommen hat. Anschließend befassen wir uns mit den Zielen jener nationalen wie europäische Institutionen, die für mehr Disintermediation und gegen das sogenannte "Overbanking" kämpfen. Schließlich betrachten wir, wie sich Disintermediation auf den Finanzierungszugang für (kleine) Unternehmen, die Wirtschaft und die Finanzstabilität auswirkt.
Keywords: E5; G2; 330; Disintermediation; loans; securities; securitization